Semiotika Visual Logo RSU.Surya Husadha Denpasar - I Nyoman Jayanegara (LPPM Institut Bisnis dan Teknologi Indonesia, 2017)
The logo is a picture mark that depicts the identity and image for the entity, where the image and corporate character are communicated with the audience by using the element of writing and image. Images and writing as a logo forming element is a sign system that aims to communicate messages about the type of business, image, or even the company's character to the public. The signs used in a logo are easily understood and conventionally agreed to be able to communicate quickly with the audience. RSU.Surya Husadha as an entity seeks to communicate the message about the type of business as well as the image of the company by using the sign system to the community. Visual signs used in the form of writing and drawing elements in the RSU.Surya Husadha logo, analyzed using semiotic theories expressed by Ferdinand de Saussure and Charles Sander Peirce. The results obtained are RSU.Surya Husadha logo has a deep philosophy about a life depicted through water and seed symbols. Life and exixtence require a balance of all the realities and consequences that exist where the philosophy is portrayed through logotype and logogram as forming elements of the company logo.